Effect of energy levels on liver oxidative state and gut microbiota of laying hens fed a low-protein diet - Mi, Qianhui; Deng, Xu; Wang, Peiying; Pan, Hongbin; Huang, Ying; Hu, Hong; Li, Anjian; Zhang, Qiang; Wang, Shaoqing (Frontiers in Animal Science, 2024)
The aim of this study was to investigate effect of energy levels on liver oxidative state and gut microbiota of laying hens fed a low-protein diet. A total of 216 laying hens (57-week-old with similar body weight) were randomly divided into 3 groups: low-energy and low-protein diet (LL: 10.73 MJ/kg), middle-energy and low-protein diet (ML: 11.15 MJ/kg), and high-energy and low-protein diet (HL: 11.57 MJ/kg) groups. The experiment lasted for 10 weeks. Results showed that the liver MDA level was higher, while the liver T-AOC level was lower in the HL group compared with LL and ML groups. The dominant phyla in LL group, ML group, and HL group were Bacteroidetes (38.08%, 39.69%, and 40.93%) and Firmicutes (16.78%, 18.37%, and 17.44%). At the genus level, Alistipes (9.45%) was abundant in the LL group. Bacteroides (14.46%), Phocaeicola (4.48%) and Precotella (2.95%) were highest in the ML group. Parabacteroides (1.78%) and Desulfovibrio (1.02%) were highest in the HL group. At the species level, Bacteroides fragilis (0.42%) is lowest in LL group, Desulfovibrio piger increased with the increase of energy. MDA was significantly and positively correlated with Methanobrevibacter woesei between ML group and HL groups (p < 0.05). T-AOC was highly significantly and positively correlated with Phocaeicola sp. Sa1YUN3 (p < 0.01). This study found that high-energy and low-protein diets might cause liver oxidative stress by gut microbes in the laying hens.